Status of an emerging viral fish pathogen Tilapia Lake Virus (TiLV) in India - Das, B K; Behera, B K; Abdulla, T; Das, A (Indian Farming, 2020)
Tilapia has been considered as the Food Fish of the 21st century and is popularly known as aquatic chicken. The world aquaculture production of tilapia is 4.0 million tonnes with an estimated value of around $ 3 billion. Food and Agriculture Organization (FAO) reports indicated that, the Global Tilapia production is expected to reach 7.3 million tonnes by 2030. Globally, Tilapia aquaculture production had reached up to 6.4 million metric tonnes.